Airway Phenotypes and Nocturnal Wearing of Dentures in Elders with Sleep Apnea. (March 2023) - Chen, H.; Emami, E.; Kauffmann, C.; Rompré, P.; Almeida, F.; Schmittbuhl, M.; van der Stelt, P.; Ge, S.; Lavigne, G.; Huynh, N.
The objective of this study was to examine to what extent the anatomic characteristics of the upper airway can influence the effect of nocturnal wearing of dentures on the sleep of edentulous elders with untreated sleep apnea. This study used the data from a randomized crossover clinical trial and an exploratory approach to address its objectives. Cone beam computed tomography scans of 65 edentulous individuals (female, n = 37; male, n = 28; mean ± SD age, 74.54 ± 6.42 y) with untreated obstructive sleep apnea (OSA) were used to identify anatomic variables. Polysomnography data were collected by means of one portable overnight recording. The respiratory variable values, including apnea–hypopnea index (AHI), with and without denture worn during sleep were used to calculate the change. Statistical analyses included multiple linear regressions, cluster analysis, and binary logistic regressions. A receiver operator characteristic curve was used to illustrate the accuracy of the statistical model. The regression model explained 15.8% ( R 2 ) of AHI change. An increase in the lateral dimension of the minimum cross-sectional area was associated with a decrease in AHI, oxygen desaturation index, and respiratory arousal index changes ( P ≤ 0.041). Furthermore, an increase in the length of the hypopharynx was associated with an increase in AHI and oxygen desaturation index changes ( P ≤ 0.027). An increase in the lateral dimension of the minimum cross-sectional area of the upper airway was associated with a decreased likelihood of being in the group having a worsened AHI (odds ratio = 0.85; 95% CI, 0.76 to 0.95; P = 0.006). An increase in the length of the oropharynx was associated with an increased likelihood of having increased AHI (odds ratio = 1.10; 95% CI, 1.01 to 1.20; P = 0.026). The nocturnal aggravation of respiratory variables in edentulous individuals with OSA who wear dentures at night can be linked to certain anatomic characteristics of the upper airway. Replication of these findings may open novel avenues for personalized advice regarding nocturnal wearing of dentures in edentulous individuals with OSA (ClinicalTrials.gov: NCT01868295).